A child with unresectable biliary rhabdomyosarcoma: 48‐month disease‐free survival after liver transplantation. (12th May 2014) - Paganelli, M.; Beaunoyer, M.; Samson, Y.; Dal Soglio, D.; Dubois, J.; Lallier, M.; Alvarez, F.
Abstract We describe here a two‐yr‐old boy with biliary RMS successfully treated by chemotherapy and LT. The child presented with obstructive jaundice at 20 months of age. A mildly vascularized, non‐calcified, partially cystic lesion was visualized in the left hepatic lobe. Solid infiltration of the common bile duct and of both left and right hepatic ducts was suspected. Liver biopsy suggested a botryoid‐type embryonal RMS originating from the biliary tract. After extrahepatic spread of the tumor was excluded, a biliary drain was applied and neoadjuvant chemotherapy was started. After the treatment, although reduced in volume, the mass was still unresectable without aggressive surgery and gross residual disease. LT with a reduced segment II/III graft was performed four months after diagnosis. The patient received six cycles of adjuvant chemotherapy, and he is alive and recurrence‐free 48 months post‐transplantation. A posteriori, the transplant might have possibly been avoided with an aggressive resection with biliary reconstruction. Nevertheless, although the risk of the transplant has to be balanced against the chemoresponsiveness of the tumor, the four‐yr disease‐free survival of this patient suggests that, when coupled with effective chemotherapy, transplantation might be considered a potential treatment for unresectable biliary RMS.